Air Quality and Sustainable Redevelopment: The Case of Construction in Dudley Square. - Abdel Rohman, Hanaa. (2017)
Abstract: Redevelopment is often shaped by community planning processes that emphasize sustainability and equity, but how does the construction process reflect the just sustainability supported in visioning stages? In this project, fine and ultrafine particles were measured and analyzed during construction of two municipal redevelopment projects in Dudley Square in order to understand the potential environmental health impacts on the surrounding community. Exposures to these particles have been linked to respiratory and cardiovascular diseases. Data were collected from the Ferdinand (July to November 2012) and the B2 Police Station demolitions (November 2014). Results showed significantly elevated levels of particles during high intensity construction days compared to low intensity construction days (p<0.001), suggesting a need for emission control strategies.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Mary Davis.; Committee: John Durant.; Keywords: Urban planning, Sustainability, and Environmental health.